[3 + 2] Cycloaddition with photogenerated azomethine ylides in β-cyclodextrin - Sohora, Margareta; Mandić, Leo; Basarić, Nikola (Beilstein Journal of Organic Chemistry, 2020)
Stability constants for the inclusion complexes of cyclohexylphthalimide 2 and adamantylphthalimide 3 with β-cyclodextrin (β-CD) were determined by 1H NMR titration, K = 190 ± 50 M−1, and K = 2600 ± 600 M−1, respectively. Photochemical reactivity of the inclusion complexes 2@β-CD and 3@β-CD was investigated, and we found out that β-CD does not affect the decarboxylation efficiency, while it affects the subsequent photochemical H-abstraction, resulting in different product distribution upon irradiation in the presence of β-CD. The formation of ternary complexes with acrylonitrile (AN) and 2@β-CD or 3@β-CD was also essayed by 1H NMR. Although the formation of such complexes was suggested, stability constants could not be determined. Irradiation of 2@β-CD in the presence of AN in aqueous solution where cycloadduct 7 was formed highly suggests that decarboxylation and [3 + 2] cycloaddition take place in the ternary complex, whereas such a reactivity from bulky adamantane 3 is less likely. This proof of principle that decarboxylation and cycloaddition can be performed in the β-CD cavity has a significant importance for the design of new supramolecular systems for the control of photoreactivity.
Keywords: [3 + 2] cycloadditions; β-cyclodextrin; inclusion complexes; photochemistry; phthalimides